Corporation finance - Anreder, Steven S. (New York : Alexander Hamilton Institute, 1967)
This text provides a panoramic view of the subject of finance, detailing the principles and techniques necessary for sound financial management.
Includes index.
hza 24/09/2018
Loans
Keywords: Corporations